The effects of the COVID-19 pandemic on pediatric dog bite injuries - Paul T. Menk; E. Melinda Mahabee-Gittens; Wendy J. Pomerantz (BMC, 2024)
Abstract Background/objective Shortly after the onset of the COVID Pandemic, when many schools and outside activities were suspended, dog adoption rates increased. It is unknown if increased dog adoption rates along with stay-at-home orders resulted in changes to pediatric dog bite injuries. The objective of this study was to examine the incidence and characteristics of dog bites in children seen in a pediatric emergency department (PED) during the pandemic compared to before. Methods A retrospective review of children evaluated in the PED of a level 1 pediatric trauma center and its satellite PED from March 2018 through February 2022 who had a discharge diagnosis of dog bite (ICD-10 W54.0XXA) was conducted. Pre-pandemic cases, March 2018 through February 2020, were compared to those that occurred during the pandemic, March 2020 through February 2022. Results There were 2,222 patients included in the study. Compared to pre-pandemic cases, the incidence for the first 12 months of the pandemic was 1.5 times higher than the pre-pandemic 12-month periods but returned closer to the pre-pandemic rates during the second 12 months of the pandemic. More patients were admitted during the pandemic (6.1% vs. 3.7%, p < 0.05). Facial and multiple injuries occurred more frequently during the pandemic (face 35.9% vs. 33.5%: multiple 18.5% vs. 15.6% p < 0.05). Conclusions There was a higher incidence of PED visits, higher admission rates, and an increase in multiple body part and facial injuries in children with dog bite injuries during the COVID pandemic compared to pre-pandemic. Pediatric providers should emphasize safe dog interactions with anticipatory guidance.